2007
DOI: 10.1186/1744-9081-3-31
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among genes in the ErbB-Neuregulin signalling network are associated with increased susceptibility to schizophrenia

Abstract: Background: Evidence of genetic association between the NRG1 (Neuregulin-1) gene and schizophrenia is now well-documented. Furthermore, several recent reports suggest association between schizophrenia and singlenucleotide polymorphisms (SNPs) in ERBB4, one of the receptors for Neuregulin-1. In this study, we have extended the previously published associations by investigating the involvement of all eight genes from the ERBB and NRG families for association with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
94
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 47 publications
11
94
2
2
Order By: Relevance
“…There are differences in details in the results between our study and others (Norton et al 2006;Benzel et al 2007), although all studies observed interaction between NRG1 and ERBB4. Norton et al (2006) observed a significant interaction between HAP ICE in NRG1 and IVS12 -15C[T in ERBB4 in a Caucasian sample.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…There are differences in details in the results between our study and others (Norton et al 2006;Benzel et al 2007), although all studies observed interaction between NRG1 and ERBB4. Norton et al (2006) observed a significant interaction between HAP ICE in NRG1 and IVS12 -15C[T in ERBB4 in a Caucasian sample.…”
Section: Discussioncontrasting
confidence: 54%
“…The IVS12 -15C[T showed no polymorphism in a Japanese population, and differences in allele and haplotype frequencies of NRG1 are remarkable between the populations (Gardner et al 2006). The difference in ethnicity or selection of SNPs may account for the difference between our result and that in Benzel et al (2007), which suggested 45 pair-wise SNP interactions between NRG1 and ERBB4 in Caucasian.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…The chromosome 10q22-q23 locus also shows linkage to schizophrenia in Ashkenazi Jewish and Han Chinese populations (2,3), and noncoding genetic variation in NRG3 has been identified as a putative risk factor for schizophrenia and related neuropsychiatric disorders (4)(5)(6)(7). Genetic association studies have also identified multiple genes and epistatic locus interactions (8) within the NRG-ErbB signaling pathway that increase risk for schizophrenia, including NRG3, NRG1, ErbB4, and AKT1, suggesting a pathogenic gene network.…”
mentioning
confidence: 99%
“…Functional NRG1 receptors therefore consist of ErbB4 homodimers, or of heterodimers between ErbB2, ErbB3 and ErbB4 (1). NRG1 and its receptors are expressed in the CNS and the NRG1, ErbB2, and ErbB4 genes are candidate susceptibility genes for schizophrenia (1,2). In the central nervous system (CNS), NRG1 is thought to regulate the differentiation of radial glia and neurons, myelination, neuronal migration and synaptic function (1).…”
mentioning
confidence: 99%